Sierra Leone Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank Group (World Bank, Washington, DC, 2021)
Sierra Leone is implementing a Medium-Term National Development Plan for 2019–2023 (2019 NDP) entitled “Education for Development”, aimed at improving people’s lives through education, inclusive growth, and the building of a resilient economy. The objective of the second Sierra Leone Report on the Observance of Standards and Codes - Accounting and Auditing (ROSC A&A) is to determine the kinds of reforms that will further strengthen the accountancy profession and enhance its contribution to the country’s growth agenda. This review focused on: (a) assessing the status of implementation of the policy recommendations and action plan developed after the first review in 2006, as well as its impact on the accountancy profession, (b) assessing and identifying any emerging issues that relate to A&A practices that require strengthening, and (c) proposing policy recommendations to strengthen the profession. The review was conducted from May to November 2019 following the revised World Bank ROSC A&A 2 methodology.